2013
DOI: 10.4314/ajtcam.v10i4.16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-inflammatory, analgesic, and antipyretic effects of ethanolic extract of <i>Pedalium murex</i> linn. fruits

Abstract: This study investigated the possible anti-inflammatory, analgesic, and antipyretic effects of ethanolic extract of Pedalium murex Linn. fruits in selected experimental animal models. Anti-inflammatory activity of Pedalium murex Linn., with doses of 200 mg/kg and 400 mg/kg, p.o., was evaluated by Lambda-carrageenan induced paw oedema in Wistar albino rats; analgesic activity with doses of 280 mg/kg and 560 mg/kg, p.o., was evaluated by hot plate method and acetic acid induced writhing method in Swiss albino mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…It is a widely used experimental model of acute inflammation that exhibits a high degree of reproducibility. 47 The characteristic swelling that occurs in the rat paw is due to increased vascular permeability and edema formation. 48 Edema induced by carrageenan is a triphasic response that involves the release of different mediators including histamine and serotonin in the first phase (1 hour).…”
Section: Discussionmentioning
confidence: 99%
“…It is a widely used experimental model of acute inflammation that exhibits a high degree of reproducibility. 47 The characteristic swelling that occurs in the rat paw is due to increased vascular permeability and edema formation. 48 Edema induced by carrageenan is a triphasic response that involves the release of different mediators including histamine and serotonin in the first phase (1 hour).…”
Section: Discussionmentioning
confidence: 99%
“…Although the present study did not determine the phytochemical composition of the test product, earlier studies elsewhere have reported that aqueous extract of A. afra possesses flavonoids [30]. Among others, flavonoids suppress cyclooxygenase activities and reduce the secretion of arachidonic acid [19].…”
Section: Discussionmentioning
confidence: 67%
“…To assess the effects of A. afra extract on thermally induced pain, a hot plate was used according to the modified protocol as previously described [19]. Rats were divided into five groups of six animals each and pretreated as described above.…”
Section: Antinociceptive Activity: Hot Plate Testmentioning
confidence: 99%
“…It is the standard experimental model of acute inflammation used to screen in vivo the antiinflammatory potential of various compounds. The method exhibits a high degree of reproducibility and allow to ascertain action mechanisms of tested substances [39]. The inflammatory condition induced by the subplantar injection of carrageenan in rats involves step-wise release of vasoactive substances such as serotonin, histamine and kinins in the early phase (0-2 h) and prostaglandins and cyclooxygenase products in the late acute phase (>3 h) [40,41].…”
Section: Discussionmentioning
confidence: 99%